Anti-apoptotic roles of plasminogen activator inhibitor-1 as a neurotrophic factor in the central nervous system - Soeda, Shinji; Koyanagi, Satoru; Kuramoto, Yukako; Kimura, Masahiko; Oda, Masatoshi; Kozako, Tomohiro; Hayashida, Satoru; Shimeno, Hiroshi (Thrombosis and Haemostasis, 2008)
Plasminogen activator inhibitor-1 (PAI-1), a member of the ser-pin gene family, is the primary inhibitor of urokinase-type and tissue-type PA s.PA I-1 plays an important role in the process of peripheral tissue remodeling and fibrinolysis through the regulation of PA activity. This serpin is also produced in brain tissues and may regulate the neural protease sequence in the central nervous system (CNS), as it does in peripheral tissues. In fact, PA I-1 mRNA is up-regulated in mouse brain after stroke.The serpin activity of PA I-1 helps to prevent tissue-type PA -induced neuron death.However, we have previously found that PAI-1 has a novel biological function in the CNS: the contribution to survival of neurites on neurons. In neuronally differentiated rat pheochromocytoma (PC-12) cells, a deficiency of PA I-1 in vitro caused a significant reduction in Bcl-2 and Bcl-XL mRNAs and an increase in Bcl-XS and Bax mRNAs.The change in the balance between mRNA expressions of the anti- and pro-apoptotic Bcl-2 family proteins promoted the apoptotic sequence: cas-pase-3 activation, cytochrome c release from mitochondria and DNA fragmentation. Our results indicate that PA I-1 has an antiapoptotic role in neurons.PAI-1 prevented the disintegration of the formed neuronal networks by maintaining or promoting neuroprotective signaling through the MAPK/ ERK pathway, suggesting that the neuroprotective effect of PAI-1 is independent of its action as a protease inhibitor. This review discusses the neuroprotective effects of PA I-1 in vitro, together with the relevant data from other laboratories. Special emphasis is placed on its action on PC-12 cells.
Keywords: Plasminogen activator inhibitor-1; neurotrophic factor; ERKrelated pathway; astrocytes; PC-12 cells